Moral hostages: refugee co-operation and burden sharing during the Indochinese refugee crisis (1975-1996) - Croke, CEJ (2015)
Why were Southeast Asian states so successful in outsourcing the costs of refugee protection during the Indochinese refugee crisis (1975-1996)? By refusing to grant asylum unless other states guaranteed to resettle refugees, this dissertation argues that real and threatened mistreatment of refugees by the states of first asylum was decisive in explaining why other states agreed to resettle them. Mistreatment of Indochinese refugees not only activated strategic concerns for the political stability of first asylum countries themselves but also affective concerns for refugee welfare. Concern about what would happen to refugees if they weren’t resettled helped sustain resettlement long after doubts arose as to whether those fleeing were truly refugees. And in the final resolution of the crisis, a concern for refugee welfare made the return of non-refugees extremely controversial. By looking at the private and public framing of the Indochinese refugees as a collective action problem for governments to solve, it demonstrates the salience of mistreatment in explaining burden-sharing. The study principally focuses on the actions of two major resettlement countries: the United States (the biggest in absolute terms) and Australia (the biggest in relative terms). Utilising extensive archival research, contemporary accounts and interviews with key policymakers of the period, it explores several distinct and important episodes over the duration of the outflow that reveal what motivated international assistance. This is descriptively important in adding to our knowledge of how refugees are treated as a question of international politics. The textural account of governmental motivation that is offered can also help test existing theoretical accounts of why governments cooperate to help refugees. Crucially, it shows that a humanitarian concern for refugee welfare both enabled and constrained co-operation.